2021
DOI: 10.1186/s40462-021-00277-3
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evaluation of the spatial scale and detection process of camera trap surveys

Abstract: Background Camera traps present a valuable tool for monitoring animals but detect species imperfectly. Occupancy models are frequently used to address this, but it is unclear what spatial scale the data represent. Although individual cameras monitor animal activity within a small target window in front of the device, many practitioners use these data to infer animal presence over larger, vaguely-defined areas. Animal movement is generally presumed to link these scales, but fine-scale heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The human effort and cost associated with sampling more than 60 placements would not be feasible in some management programmes, which may limit the applicability of REM for wildlife monitoring (but CV of <0.2 may not always be necessary’). In this respect, some studies have shown seasonal variation in encounter rates (Kays et al., 2021; Kolowski et al., 2021), so a general recommendation when applying REM could be to survey populations when low aggregation is expected. This could help to optimise human effort.…”
Section: Discussionmentioning
confidence: 99%
“…The human effort and cost associated with sampling more than 60 placements would not be feasible in some management programmes, which may limit the applicability of REM for wildlife monitoring (but CV of <0.2 may not always be necessary’). In this respect, some studies have shown seasonal variation in encounter rates (Kays et al., 2021; Kolowski et al., 2021), so a general recommendation when applying REM could be to survey populations when low aggregation is expected. This could help to optimise human effort.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate how recreational activities impacted wildlife habitat use, we modeled the “probability of use” (Kays et al, 2021 ) for each of these focal species during a station‐week with a Bayesian generalized linear mixed‐effects model (GLMM), assuming a binomial response distribution and including station as a random intercept to account for non‐independence among weeks sampled at the same station. Using this GLMM specification, the probability of use of a station during each week for each species was modeled as a function of several hypothesized explanatory variables (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore assumed that the potential influence of variation in detectability was minimized by our standardized protocols and inclusion of these sampling variables. We did not use an occupancy modeling approach to estimate detectability, as we were interested in variation in detections as a signal of local habitat use rather than as detection error, and we considered it unlikely that the assumptions of occupancy modeling would be met in our sampling context (e.g., site closure; Neilson et al, 2018 ; Kays et al, 2021 ). We assumed any temporal autocorrelation was accounted for through the inclusion of the random effect of camera station, and tested for spatial autocorrelation among stations using Mantel tests on model residuals.…”
Section: Methodsmentioning
confidence: 99%
“…Missed detections could potentially generate misleading results in camera trapping studies, and therefore, create difficulties as regards direct comparison among studies (Jacobs & Ausband, 2018). In this respect, despite some statistical approaches accounting for the imperfect detection (Guillera-Arroita et al, 2010), recent studies have shown that biased and imprecise results can be obtained when detection probabilities are low (Hofmeester et al, 2021;Kays et al, 2021). Additionally, (1) there are a wide variety of studies that used the raw encounter rates without accounting for false-negatives (i.e.…”
Section: Introductionmentioning
confidence: 99%